2018
DOI: 10.1021/acssuschemeng.7b03999
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Recovery from Bilberry (Vaccinium myrtillus L.) Presscake via Microwave Hydrolysis

Abstract: Bilberry presscake, a byproduct from juice production, contains abundant polysaccharides that can be recovered by thermal treatment. In this research, microwave hydrolysis and extraction were carried out using only water as the processing medium, thus ensuring all products (mainly saccharides) are suitable for food grade status applications. This research aims to propose an approach to fulfill multiple chemicals recovery, including anthocyanins, saccharides, proteins, and even inorganic salts. Statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The exploitation of V. myrtillus fruits for medicine and human diet purposes has gained significant attention, being the economically most important wild berries of Northern Europe, widely used by the food industry [94]. This fruit is consumed not only in a fresh manner, but also in processed products (press cake) and derivatives (juice, jam and liqueur) [95,96]. Fruits drying and its transformation into powder represent a suitable alternative widely used by consumers and the food industry that allow having them available throughout the year for subsequent use as an ingredient in based foods (extruded products, bakeries, sauces, beverages, ice creams, yogurts, and confectionary) [11,97].…”
Section: Industrial Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploitation of V. myrtillus fruits for medicine and human diet purposes has gained significant attention, being the economically most important wild berries of Northern Europe, widely used by the food industry [94]. This fruit is consumed not only in a fresh manner, but also in processed products (press cake) and derivatives (juice, jam and liqueur) [95,96]. Fruits drying and its transformation into powder represent a suitable alternative widely used by consumers and the food industry that allow having them available throughout the year for subsequent use as an ingredient in based foods (extruded products, bakeries, sauces, beverages, ice creams, yogurts, and confectionary) [11,97].…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…The by-products resulting from the production of bilberries, as well as the fruits that, due to their exterior appearance or size do not meet commercialization standards, may also be used for the preparation of polyphenols extracts and the production of novel foods, conferring them added value and reducing the environmental impact. Some authors showed that the press cake of V. myrtillus , a by-product of juice production, can be a suitable and green approach to be used in the preparation of value-added products by the food industry [ 96 , 98 , 99 ]. For instance, Fidaleo et al [ 33 ] studied the suitability of phenolic extracts obtained from V. myrtillus residues as an ingredient in drinking yogurt and condensed milk with a high antioxidant capacity [ 33 ].…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…Furthermore, the peak around 1638 cm À1 is related to the C ¼ O group of the molecules from fruit extract [43]. The absorption peaks in the region between 1050 and 1200 cm À1 are attributed to C-O stretching vibrations of alcohols and carboxylic acids of the extract [44]. The Zn-O bond stretching vibration appeared at 530 cm À1 [45,46].…”
Section: Characterizationmentioning
confidence: 99%
“…[10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake. [15] The mosts tudied and highest yielding biomass precursor for the synthesis of LGO is cellulose. One of the earliest syntheses that correctly characterized the structure of LGO wasa ccomplished in 1973 by Broido and coworkers, who used ap yrolysis methodf or the decomposition of cellulose.…”
Section: Synthesis Of Levoglucosenone and Cyrenementioning
confidence: 99%